Makna Imperatif Struktural dan Nonstruktural dalam Novel Anak Berbahasa Inggris Hello Universe Karya Erin Entrada Kelly - Afni Apriliyanti Devita; Wahya Wahya; Nani Darmayanti (LP4MK STKIP PGRI Lubuklinggau, 2020)
One of the literary works for children that can be used as a medium for learning English is novel. The children's novel tells the children's worlds and thoughts. The method used in this research is examine the imperative form of speech in the English children's novel Hello Universe by Erin Entrada Kelly with a pragmatic study. The object or data of this research is the imperative structural and non-structural speech in the novel. The technique of collecting data was done by using the observation technique and noting technique from the novel. The data analysis used the distributional and identity method with the Segmenting Immediate Constituents technique and Dividing Key Factors technique with pragmatic competence-in-dividing technique, namely reading imperative sentences in the novel, classifying structural imperative sentence types, analyzing data based on the form and function of imperative speech, and summarize research results. The data validity was checked through membercheck and pragmatic expert test. Based on the research results, it was found that the form of utterance with imperative meaning consists of declarative sentences, interrogative sentences and imperative sentences. The meaning of the imperative can be found in non-structural imperative sentences in the form of declarative and interrogative sentences. The use of imperatives in this novel uses more direct speech because the conversation is in non-formal children's friendship situations. The structural imperative speech function is mostly a command. Meanwhile, the interrogative sentence mostly has a function as a request and declarative sentences mostly has a function as a suggestion.